Poetics of Authenticity - Burenius, Axel (2023)
Based on tape-recorded interviews with a multitude of historical eyewitnesses, Svetlana Aleksievich’s five-volume literary project Golosa utopii depicts some of the most calamitous events of Soviet history – the Second World War, the Soviet-Afghan war, the Chernobyl nuclear disaster, and the dissolution of the Soviet Union. This thesis seeks to provide the first systematic study of the different social, historical and cultural factors which have shaped Aleksievich’s genre-transgressive writing, which is marked by both historiographical and literary aspirations. This thesis examines the development of Aleksievich’s complex aesthetics in the context of the documentary tradition in Russian and Soviet culture, including her engagement with such prominent predecessors in the literary canon as Fedor Dostoevskii, Aleksandr Solzhenitsyn, Varlam Shalamov, and Ales’ Adamovich. I argue that Aleksievich’s continuous insistence on the ‘truth’ and ‘authenticity’ of her work is central to her thinking and writing. This thesis demonstrates that these key concepts emerge during her work as a journalist for the Soviet press – an apprenticeship which would also leave clear traces in her practice as a writer. This historical, cultural and social context is crucial to understanding Aleksievich’s construction of a particular public persona in the later stages of her career. I therefore examine Aleksievich’s strategies of positioning herself as a non-conformist writer exposing the untruths of the official Soviet discourse, including Soviet newspapers, which are foregrounded as the negative other of her own discourse. Analysing her employment of counter-narratives using a Bordieuan framework, I examine the truth-claims underpinning her public persona as a dissident writer ‘giving a voice’ to the repressed. The interplay between authorial voice and the many witnesses in her books underpins both this self-portrayal and the claim to the authenticity and truth of her work. This thesis examines the multi-voiced structure of Aleksievich’s works against the backdrop of Mikhail Bakhtin’s concept of literary polyphony and analyses the authorial interventions in her texts. Focusing on the historical, cultural and literary context of the production and reception of Aleksievich’s work, this thesis presents the first systemic study of the complex strategies by which Aleksievich authenticates and legitimizes her claims to present a higher form of truth in her literary-historiographical project Golosa utopii.